101 Dispelling the curse: improvement of ventilatory drive in central alveolar hypoventilation syndrome after medullary infarction. Issue 6 (24th May 2018) - Fedi, Marco; Shen, Shi Hong; Campbell, Bruce; Dutschmann, Mathias; O'brien, Terrence; Anstey, James; MacIsaac, Christopher
Abstract : Introduction: Central alveolar hypoventilation syndrome (CAHS) is a rare complication of stroke affecting the medullary respiratory centre. CAHS is characterised by impaired ventilatory response to CO2 leading to hypoventilation, hyper-capnoea and coma. Experimental studies have linked this syndrome to areas in the dorsal and ventrolateral medulla. CAHS is associated with long-term invasive ventilatory support, high mortality and morbidity. It is unclear whether sensitivity to CO2 can improve after the initial ischaemic medullary insult. Case: A 78 year old woman presenting with CAHS secondary to a unilateral left posterior inferior cerebellar artery infarction. MRI images confirmed that dorsal and ventrolateral medullary areas were affected. The patient was intubated initially for hyper-capnoeic respiratory failure and required a tracheostomy for ongoing respiratory support. To assess progress of respiratory recovery, we measured the patient's ventilatory response to PaCO2 at 5, 7, and 14 days of admission. Parameters recorded included PaO2, ETCO2, PaCO2, pH, respiratory rate, and minute ventilation. During this time the patient underwent progressive periods of unsupported ventilation with close monitoring. Statistical correlation between respiratory rate and CO2 was measured by Pearson's correlation coefficient (R). Her RR initially did not increase with PaCO2 during spontaneous ventilation (R=0.2604 p=0.077). Apnoeic episodes were frequent up to 41 episodes per 30 min of observation lasting up to 30 s. On day 7(R=0.7203 p<0.05) and up to day 14 (R=0.6295 p<0.05), there was a progressive statistically significant improvement in positive correlation between PCO2 and respiratory rate. This was associated with a reduction in apnoeic episodes possibly reflecting a recovery in ventilatory drive. Conclusion: This is the first detailed report demonstrating spontaneous recovery in CO2 responsiveness in the setting of CAHS secondary to unilateral medullary stroke. Plasticity of structures such as the retro-trapezoid nucleus are likely to play a role in recovery of CO2 sensitivity. References: . Harper, et al. Functional neuroanatomy and sleep-disordered breathing: implications for autonomic regulation. Anatomical record2012;295(9):1385–95. . Mishina, et al. Efficacy of tracheostomy for central alveolar hypoventilation syndrome caused by lateral medullary infarction. Journal of Nippon Medical School2014;81(4):276–84.